The republic - Plato (Floating Press, 2009)
The Republic is Plato's most famous work and one of the seminal texts of Western philosophy and politics. The characters in this Socratic dialogue - including Socrates himself - discuss whether the just or unjust man is happier. They are the philosopher-kings of imagined cities and they also discuss the nature of philosophy and the soul among other things.